1985
DOI: 10.1103/physreva.31.1046
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of ionizing electron shock waves in electrical breakdown

Abstract: A numerical solution of a hydrodynamic second-order model shows that the propagation of the first ionizing wave arises from an overgrowth of hot electrons in the wave front in a zone of a greatly disturbed electric field. This gives rise, in the electron shock zone ahead of the wave, to a precursor phenomenon, whose effect is to accelerate the channel propagation. Inside the shock zone, the electronic energy differs from the characteristic energy; the nonequilibrium between the electrons and the electric field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…To make contact with previous work [42,47,48,50], we here present different forms of equations (29)- (32). When we evaluate the averages over the velocities c in these equations and perform a considerable amount of algebra, we find…”
Section: Appendix a Alternative Forms Of The High Order Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…To make contact with previous work [42,47,48,50], we here present different forms of equations (29)- (32). When we evaluate the averages over the velocities c in these equations and perform a considerable amount of algebra, we find…”
Section: Appendix a Alternative Forms Of The High Order Modelmentioning
confidence: 99%
“…The first important steps beyond first order fluid models of streamer discharges, to our knowledge, were carried out by Abbas and Bayle [46,47], and by Bayle and Carenbois [48]. They employed a second order model which involves the energy balance equation to explore the zone at the streamer tip where the electron energy is not determined anymore by the local electric field only.…”
Section: Second Order Models Including the Energy Balance Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this time the voltage dropped at least 40% of the maximum value. The discharge voltage then remained at this low level for [10][11][12][13][14][15][16][17][18][19][20] s, before slowly rising back to the initial voltage. Measurements of the voltage divider signal indicated that despite the high source voltage ͑defined as the voltage at the power supply͒ in the range from 1 to 4.8 kV, the actual potential across the needle ranged approximately from 300 to 450 V. The average current through the source increased with the source voltage, and was in the range from 15 to 85 A.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many experiments concerning the properties of corona discharges have been conducted [13][14][15] ͑for an insightful overview on mechanisms of coronas see Loeb 16 ͒ and extensive theoretical literature exists regarding these discharges. 13,[17][18][19] However, the typical configuration for creating atom beams differs considerably from experiments on the properties of corona discharges. In the latter, discharges occur at high uniform pressures in ideal point-to-plane or point-to-cylinder electrode geometries.…”
Section: Introductionmentioning
confidence: 99%